Trenggalek dalam Panggung Budaya Masa Lampau di Jawa Bagian Selatan: Ragam dan Karakternya - Hery Priswanto; Muhammad Chawari; Alifah Alifah; Mudjijono Mudjijono; Agus Prasmono (Badan Riset dan Inovasi Nasional (BRIN), 2023)
Trenggalek Regency is one of the regencies of East Java Province located in the southern part of Java Island. Trenggalek Regency is surrounded by Tulungagung, Pacitan, and Ponorogo Regencies which have abundant cultural heritage potential, Trenggalek Regency has the potential for archaeological remains as many as 17 points. Archaeological research in Trenggalek Regency was initiated by the Yogyakarta Archaeological Center in 1983 in the form of surveys or excavations that continued until 2020. The purpose and purpose of writing this article is to know the variety and character of cultural heritage in Trenggalek. This article data was obtained through an archaeological survey in eight sub-districts in Trenggalek Regency in 2020. Based on the results of the study, Trenggalek Regency has a variety and character including the form, distribution of locations, and chronology of its cultural heritage. Archaeological data in the form of moveable and monumental artifacts and features. The dominance of moveable artifact data is in the form of stone piles, stone dies, terracotta pole shell fragments, dakon stones, and Yoni while monumental artefactual data in the form of pillboxes and inscriptions. Chronologically, the discovery of objects suspected of cultural heritage in Trenggalek Regency shows the influence of Hindu-Buddhist until the Islamic Mataram era of the Ngayogyakarta Hadiningrat Sultanate around the XIX century AD. Keywords: Trenggalek; Panggul; yoni; dakon stone; pillbox